Trend of Academic Flow in Adolescence - Irfan Fahriza; Nur Baitillah; Nabila Qurrotu Aini; Syari Fitrah Rayaginansih (Ma'soem University, 2022)
Academic flow is one of the determining factors for the success of the learning process. This study aims to determine trends in academic flow before, during, and after the end of the pandemic. This study uses a literature review as a data collection tool. The results showed differences in the condition of academic flow in adolescents and factors that influenced both internal and external. During the pandemic, junior high school Adolescence academic flow tended to be at a moderate level, while high school Adolescence academic flow was at a low level. After the pandemic, conditions in junior high school youth tended to be at a low level. Internal factors that affect academic flow conditions are self-awareness, resilience, academic competence, intelligence categorization, religiosity, achievement motivation, self-efficacy, and self-regulated learning. At the same time, external factors are social support, peer and teacher support, learning methods, and the environment. In increasing academic flow, anchor for flow can be an effective technique.